Mechanical Properties of Glued-Laminated Timber with Different Assembly Patterns - Shan Gao; Man Xu; Nan Guo; Ying Zhang (Advances in Civil Engineering)
A glued-laminated timber section with mixed-grade laminae could make an efficient use of material strength and reduce the cost. A 4-point bending test was conducted on a total of 18 specimens to investigate the mechanical properties of glued-laminated timber. Uniform-grade, asymmetrical mixed-grade, and symmetrical mixed-grade patterns were used to assemble the beam sections. The bending stiffness and reliability of the beams were assessed according to the experimental results. The influence of the assembly pattern on the bending behavior of glued-laminated timber was investigated by finite element models. The results show that the assembly pattern of the section has little influence on the failure mode of glued-laminated timber. Relative lower strength in compressive area of the section is beneficial for delaying the occurrence of the first crack on the glued-laminated timber beam. An equation for apparent bending stiffness of glued-laminated timber was proposed, whose results match well with the experimental results. The beam section assembled by the asymmetrical mixed-grade pattern retains the higher level of safety compared to those assembled by uniform-grade and symmetrical mixed-grade patterns. The grade of the second bottom lamina in tensile has little influence on the performance of glued-laminated timber, while lower grade laminae in compressive area of the section would cause a bending stiffness reduction at smaller deflection.